(untitled) (Progressive Agriculture, 2017)
An experiment was carried out to study the density dependent growth of Thai sharpunti (Barbonymusgonionotus) for two months period. Three stocking densities such as 50/decimal, 100/decimal and 150/decimal representing treatment one (T1), treatment two (T2) and treatment three (T3), respectively were tested in three replications. A commercial diet (25% crude protein) was supplied twice daily throughout the study period up to satiation level. The total production of sharpunti was found 14.67 ± 2.05, 27.06 ± 3.09 and 36.87 ± 2.16 kg/decimal in T1, T2 and T3, respectively and they were significantly different (p<0.05) from each other. A higher net benefit of BDT 1079.50 was obtained from T2 where the stocking density was 100/decimal. The present study indicated that the growth and production of Thai sharpunti was density dependent in monoculture systems. Progressive Agriculture 28 (3): 249-252, 2017